Contagion of pro- and anti-social behavior among peers and the role of social proximity - Eugen Dimant (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2018)
This paper uses a novel experimental design to study the contagion of pro- and antisocial behavior and the role of social proximity among peers. Across systematic variations thereof, we find that anti-social behavior is generally more contagious than pro-social behavior. Surprisingly, we also find that social proximity amplifies the contagion of anti-social behavior more strongly than the contagion of pro-social behavior, and that anti-social individuals are most susceptible to behavioral contagion of other anti-social peers. These findings paired with the methodological contribution are informative for the design of effective norm-based policy interventions directed at facilitating (reducing) pro- (anti-)social behavior in social and economic environments.
Keywords: C91; D64; D9; 330; Behavioral Contagion; Peer Effects; Anti-Social & Pro-Social Behavior